2019
DOI: 10.1634/theoncologist.2019-0636
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogression and Immune Checkpoint Inhibitors: Hype or Progress?

Abstract: There are currently seven approved immune checkpoint inhibitors (ICIs) for the treatment of various cancers. These drugs are associated with profound, durable responses in a subset of patients with advanced cancers. Unfortunately, in addition to individuals whose tumors show resistance, there is a minority subgroup treated with ICIs who demonstrate a paradoxical acceleration in the rate of growth or their tumors-hyperprogressive disease. Hyperprogressive disease is associated with significantly worse outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 56 publications
(141 reference statements)
1
39
0
3
Order By: Relevance
“…The amplified genes ( MDM2 / MDM4 / CCND1 / FGF3 / FGF4 / FGF19 ) have been suggested as genomic correlates of increased risk of hyperprogression after immune checkpoint inhibitors ( 19 ). Another study reported that CDK4 copy number gain was negatively correlated with anti-PD1 response in all subtypes of advanced melanoma and CCND1 copy number gain was associated with a lack of response to anti-PD-1 therapy in advanced acral melanoma ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…The amplified genes ( MDM2 / MDM4 / CCND1 / FGF3 / FGF4 / FGF19 ) have been suggested as genomic correlates of increased risk of hyperprogression after immune checkpoint inhibitors ( 19 ). Another study reported that CDK4 copy number gain was negatively correlated with anti-PD1 response in all subtypes of advanced melanoma and CCND1 copy number gain was associated with a lack of response to anti-PD-1 therapy in advanced acral melanoma ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the proportion of “responder” patients—that is to say, in whom the treatment is effective—varies considerably from one cancer to another. It can reach 40% in melanoma and is between 20% and 30% in the lung, but only 1% of patients with pancreatic cancer are responders [ 116 , 117 ]. This disparity could be explained by the fact that the immune system must recognize the tumor as a foreign body that needs to be eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…No validated clinical or molecular predictors of HPD have been identified due to the heterogeneity and retrospective nature of the studies. Furthermore, there is no consensus on HPD definition and distinct criteria (i.e., one-dimensional, volumetric or clinical) have been proposed (15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%